A General Decision Model for Cost-Volume-Profit Analysis Under Uncertainty: A Reply. - Shih, Wei (The Accounting Review, 1981)
Abstract The article presents the reply of the author to the article by D.R. Finley, assistant professor of accounting and Woody M. Liao, associate professor of accounting, published in the April 1981 issue of the journal "The Accounting Review," on author's general decision model. According to the author, the decision criteria developed by Finley and Liao for determining a product's marketability under normally distributed demand is a valid and smooth integration of equations derived in author's paper. Their decision criterion calls for a positive expected profit as a precondition for marketing a product. Such an approach to the break-even analysis under uncertainty has several major limitations. The first major limitation is that their decision criterion failed to take into account the decision maker's attitude toward risk-taking. The second major limitation of the choice criterion proposed by Finley and Liao is that it is a very pessimistic and highly inflexible approach. Such a negative and rigid view of uncertainty, will certainly be detrimental to the expansion and development of any business endeavors.